2014
DOI: 10.1080/15401383.2014.892864
|View full text |Cite
|
Sign up to set email alerts
|

The Process of Therapeutic Reading: Opening Doors for Counselor Development

Abstract: In this study, the authors examined the therapeutic reading process with graduate counseling students. Journals completed by 21 students participating in a graduate counselor education elective course, Creativity in Counseling, were examined. Phenomenological data analysis approaches were employed. Emergent themes suggested that therapeutic reading opened doors for insight, action, connection, communication, building relationships, and growth as professional counselors. Implications for counselor education, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
(29 reference statements)
0
1
0
1
Order By: Relevance
“…These results suggest that the story reading has negative impact on symptoms of mental illnesses and even may function as a factor to prevent mental health problems in schools. Available evidence showed that those therapeutic approaches have various benefits to readers, from reduced loneliness and isolation to mitigated depressive symptoms (Bruneau & Pehrsson, 2014 ). The benefits of therapeutic reading in reducing depression and anxiety have been documented in different populations including adolescents and adults (Scogin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that the story reading has negative impact on symptoms of mental illnesses and even may function as a factor to prevent mental health problems in schools. Available evidence showed that those therapeutic approaches have various benefits to readers, from reduced loneliness and isolation to mitigated depressive symptoms (Bruneau & Pehrsson, 2014 ). The benefits of therapeutic reading in reducing depression and anxiety have been documented in different populations including adolescents and adults (Scogin et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Temuan penelitian mengenai pemanfaatan bacaan untuk keuntungan terapeutik atau dikenal dengan biblioterapi menunjukkan berbagai manfaat bagi pembaca mulai dari yang dinyatakan bebas dari kesepian dan isolasi hingga penurunan gejala depresi. Peneliti lain menemukan bahwa pembaca menunjukkan peningkatan kesadaran budaya, peningkatan koping religius, peningkatan pemahaman empatik, keterampilan pemecahan masalah yang lebih baik, dan keuntungan keseluruhan dalam meningkatkan wawasan (Bruneau & Pehrsson, 2014;Dewi & Widiyanti, 2018;Fitriyani & Dewi, 2017;Pardini et al, 2014). Hasil ini menguatkan intervensi TBQ dapat membantu individu untuk menghargai diri mereka sendiri, menemukan cara untuk mengembangkan diri, dan menangani hal-hal sulit dengan cara yang lebih kreatif, terutama bagi individu yang mengalami gangguan emosi atau mental, dengan dilandasi oleh nilai-nilai Ilahiyah.…”
Section: Pengaruh Biblioterapi Islami Terhadap Kesehatan Mental Wanitunclassified